Describing a COVID-19 Case and Presenting the Proposed Plan to Recovery - Nadhmi Al-Doori, Ahmed; S. Ahmed, Dina (Al-Nahrain Journal of Science, 2021)
The current outbreak of serious respiratory syndrome (aka COVID-19) has resulted from a novel coronavirus (SARS-CoV-2). This infectious disease was classified as a pandemic by the World Health Organization (WHO) because it threatens public health and life worldwide. Recently, restrictions in many countries are applied to detect the infected individuals, isolate them, and attempt to find appropriate treatments that can help decrease the disease’s severe symptoms. Regardless of the conducted efforts, the number of reported cases of coronavirus infections is still growing up.